Perpetual ‘Outcasts’?: Squatters in peri-urban Bulawayo, Zimbabwe - Mpofu, Busani (Afrika Focus, 2012)
After independence in 1980 Zimbabwe’s cities experienced a proliferation in the number of squatter camps. This was because of the failure of the urban economy to offer adequate housing and jobs, leaving peri-urban space as the only sanctuary for the urban poor to live in and eke out a living informally. The promotion of rural ‘growth points’ by the national government to promote rural development to discourage migration to urban areas failed. Yet, a poor policy response by the state to this negative outcome of rapid urbanisation that aims to reverse this rural-urban migration has led to unending confrontations between its various arms and squatters who continue to be regarded as encroachers. Focussing on Bulawayo, the second largest city in Zimbabwe, and based on interviews, archival research, Council minutes and newspapers, this article critiques the state’s urban development policy vis-à-vis squatters and informality. It is argued that the persistence of a salient perception by government officials that all Africans belong to rural areas and have access to land they can fall back on in hard times serves as a vital lubricant to the state’s action of forcibly sending squatters to rural areas. This ignores the historical pattern of rapid urbanisation and the growth of informal economies supporting the livelihoods of thousands of people. I seek to add to the literature on low-cost housing shortages, urban squatters and peri-urbanism in Zimbabwe and on studies of informality in Third World cities in general.